The biodegradation of low-density polyethylene by Bacillus species - Felicia E. Uwakwe; Tobias I.N. Ezejiofor; Ernest A.A. Anyalogbu; Toochukwu E. Ogbulie (EQA)
Polyethylene (PE) products have short-term applications, resulting in the daily release of enormous quantities of plastic wastes into the environment with their attendant public and environmental health threats of global concern. Developing an eco-friendly management method to abate the menace prompted this research work. Four Bacillus species were isolated from different dumpsites in Owerri Metropolis, and identified using 16S rDNA sequencing, as B.pumilus, B.siamensis, B.coagulans and B. subtilis. The ability of the microbial isolates to degrade polyethylene (table water sachets) was determined using microbial growth measurement in liquid medium (Optical Density (OD600)), disappearance and introduction of functional groups (Fourier Transform Infrared spectroscopy (FTIR) and weight loss analysis measured after sixty (60) days of incubation in mineral salt vitamin media. Microbial density showed a gradual and progressive increase from 0 day to 60 days : B. siamensis (0.12 - 0.84), B.pumilus (0.11-.67), B.coagulans (0.12 - 0.61) and B.subtilis (0.11 – 0.60), as against the control medium which remained unchanged (0.11). Similarly, FTIR spectra showed additional functional groups (carboxylic acids, ethers, esters, amines, methylene, alcohols, and alkenes in the polyethylene materials exposed to the test isolates: B.siamensis (17 peaks), B.pumilus (12 peaks), B.coagulans and B.subtilis (13 peaks each), but control (8 peaks). There were subatantial reduction in the residual weights of the PE materials: B.siamensis (52%), B.pumilus (26%), B.coagulans and B.subtilis (18% each). The observations showed that these Bacillus spp. indigenous to Owerri Metropolis have the ability to degrade PE and utilize it as a carbon source, and it was concluded that biodegradation was achieved, and that PE which was regarded to be inert can be biodegraded when exposed to the right microorganisms.